Finite element based large eddy simulation of flow over bluff bodies. (24th November 2017) - Tran, Steven; Cummings, Reed; Sahni, Onkar
Highlights: Finite element based large eddy simulation of complex inhomogeneous turbulent flows. Combined subgrid-scale model based on the RBVMS and Smagorinsky models. Dynamic procedure based on a localized version of the variational Germano identity. Combined model based LES data is in agreement with experimental and DNS datasets. Abstract: Large eddy simulation (LES) of bluff body flows is performed using a finite element based formulation which employs a combined subgrid-scale model. The combined model uses the residual based variational multiscale (RBVMS) approach along with the dynamic Smagorinsky eddy viscosity model. Specifically, the RBVMS model is used to represent the cross-stress terms while the dynamic eddy viscosity model is used for the Reynolds stresses. The dynamic procedure is based on a localized version of the variational Germano identity. Two sets of cases are considered: flow over straight and wavy circular cylinders at R e D m = 3000, and flow over a straight square cylinder at R e D = 22, 000 . For the straight circular cylinder case, we compare LES predictions based on the RBVMS model and the combined subgrid-scale model against the experimental data. The combined model provides better predictions (for both force data and centerline profiles in the wake) and we select it in the rest of the cases. For the wavy circular cylinder case, LES predictions (based on the combined model) shows a good agreement with the experimental data including mean velocity profiles in the wake. It accurately captures the elongation of the recirculation region. In the square cylinder case too, LES predictions (based on the combined model) show a very good agreement with the direct numerical simulation and multiple experimental datasets.